Influence of Trace Mineral Sources and Levels on Growth Performance, Carcass Traits, Bone Characteristics, Oxidative Stress, and Immunity of Broiler - Tassanee Trairatapiwan; Rachakris Lertpatarakomol; Sucheera Chotikatum; Achara Lukkananukool; J. Mitchaothai (Animals, 2025)
= 0.02). No significant differences were observed in oxidative stress markers or IgG levels among groups. This study demonstrated that reducing the inclusion level of inorganic trace minerals did not negatively affect broiler growth performance, whereas supplementation with low levels of organic trace minerals improved both growth performance and carcass quality.
Keywords: Moringa oleifera research and applications; Animal Nutrition and Physiology; Rabbits: Nutrition, Reproduction, Health